Bem-estar alimentar e vegetarianismo: um estudo sob a perspectiva da Pesquisa Transformativa do Consumidor - Alves, Pollyana Soares (2019)
Food consumption decisions resulting from the population's lifestyle are related to symbolic dimensions, reflected in food practices that make up social groups. Thus, the objective of this dissertation was to analyze the food well-being, proposed by Block et al. (2011) from the context of the eating habits of vegetarians. Concerning the perspective of the Transformative Consumer Research, this study sought to propose transformative reflections, making possible to wide the understanding about food well-being within the vegetarian subculture. Regarding methodological procedures, the qualitative research approach was adopted. The chosen research method was oral history, using individual interviews with a semi-structured script, anchoring the methodological course based on the use of content analysis. A group of 16 adult individuals, who were adept to vegetarianism, was selected from several brazilian states. Moreover, an observation step was carried out in order to proceed with systematic records for the aforementioned phenomenon. The results of this research indicated that vegetarian consumers have sought to acquire products that promote greater well-being, based on their food consumption behaviors, in which impacts on the promotion of food well-being were evidenced through transformative practices. Therefore it is essential to capture how food well-being is constructed and perceived, as well as its meaning for individuals in the process of structuring food consumption practices in order to boost and collaborate with new studies in the area of consumer well-being